Girl Head : Feminism and Film Materiality. - Yue, Genevieve (New York : Fordham University Press, 2020)
Girl Head shows how gender has had a surprising and persistent role in film production processes, well before the image ever appears onscreen.
Intro -- Title Page -- Copyright -- Dedication -- Contents -- List of Plates and Figures -- Introduction: The Body of Medusa -- 1. China Girls in the Film Laboratory -- 2. Gone Girls of Escamontage -- 3. Gradivan Footsteps in the Film Archive -- Afterword -- Color Plates -- Acknowledgments -- Notes -- Bibliography -- Index -- About the Author
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Feminism and motion pictures; Motion pictures and women; Film criticism; Féminisme et cinéma.; Cinéma et femmes; Critique cinématographique.; Feminism and motion pictures; Film criticism; Motion pictures and women